Effect of salts from the lyotropic series on the handling properties of dough prepared from two hard red spring wheat cultivars of differing quality. (1st August 2020) - Avramenko, Nicole A.; Hopkins, Erin J.; Hucl, Pierre; Scanlon, Martin G.; Nickerson, Michael T.
Highlights: Pembina doughs were stronger and less sticky than Harvest. Salt-type was cultivar dependent for how it affected rheology and stickiness. Cultivar appears to affect link between dough stickiness and water association. Pembina flour appears less sensitive to salt-type changes than Harvest. Abstract: The influence of select salts from the lyotropic series (NH4 Cl, KCl, NaCl, MgCl2, CaCl2, and MgSO4 ) on the rheology and stickiness of dough prepared from a strong (Pembina) and a weak (Harvest) hard red spring wheat flour were examined at a 1 and 2% salt levels, with water mobility and water association with different dough components also being assessed at the 1% salt level. Overall, Pembina was found to develop stronger gluten networks that were more resilient than those of Harvest as evident from a lower tan δ and less compliance during shear creep recovery rheology. However, the effect of salt-type differed based on cultivar. Pembina showed lower dough stickiness than Harvest in all cases. NH4 Cl decreased dough stickiness the most for both cultivars. The use of alternative salts affected the association of water with the starch-fraction and gluten-fraction in doughs, and this effect was cultivar-dependent.